Emerging patterns of infant regulatory behavior in the Still-Face paradigm at 3 and 9 months predict mother-infant attachment at 12 months. Issue 6 (2nd November 2021) - Barbosa, Miguel; Beeghly, Marjorie; Moreira, João; Tronick, Ed; Fuertes, Marina
ABSTRACT: Prior research described three stable patterns of organized behavior employed by infants to manage stressful interactive situations with their mothers in the Face-to-Face Still-Face paradigm (FFSF) at 3 and 9 months postpartum. The current longitudinal study expands this research by examining the extent to which these patterns predict infants' later attachment quality. For that purpose, 108 full-term infants and their mothers participated in the FFSF at 3 and 9 months, and in the Strange Situation at 12 months. Cross-tabulation analyses indicated a significant association between (1) the Social-positive oriented pattern and secure attachment, (2) the Distressed-inconsolable pattern and insecure-ambivalent attachment, and (3) the Self-comfort oriented pattern and insecure-avoidant attachment. Our results contribute to a growing body of studies suggesting that patterns of infants' regulatory behavior assessed during the FFSF during the first year, may be early developmental precursors of attachment patterns at 12 months.